1991
DOI: 10.2307/1131177
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Conversation in Different Social Classes and Communicative Settings

Abstract: 30 working-class and 33 upper-middle-class mothers were videotaped in dyadic interaction with their 18-29-month-old children in 4 settings--mealtime, dressing, book reading, and toy play. Samples of the mothers' adult-directed speech also were collected. There were significant social class differences in the mothers' child-directed speech and some parallel social class differences in the mothers' adult-directed speech. These findings suggested that some social class differences in child-directed speech may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
268
5
19

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 520 publications
(305 citation statements)
references
References 20 publications
13
268
5
19
Order By: Relevance
“…Previous studies with English-speaking families in the United States and French-speaking Canadian families demonstrated that shared book reading in particular can be a source of vocabulary learning (Ewers & Brownson, 1999;Sénéchal, 2006a) because children's books in English tended to contain more rare, academic words than those found in television or conversations (Hayes & Ahrens, 1988). Furthermore, mothers may use richer and more varied vocabulary during shared reading (Hoff-Ginsberg, 1991;Snow & Ninio, 1986). Children's experience with print also provides opportunities for a child to recognize letters, thus enhancing their letter-name knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with English-speaking families in the United States and French-speaking Canadian families demonstrated that shared book reading in particular can be a source of vocabulary learning (Ewers & Brownson, 1999;Sénéchal, 2006a) because children's books in English tended to contain more rare, academic words than those found in television or conversations (Hayes & Ahrens, 1988). Furthermore, mothers may use richer and more varied vocabulary during shared reading (Hoff-Ginsberg, 1991;Snow & Ninio, 1986). Children's experience with print also provides opportunities for a child to recognize letters, thus enhancing their letter-name knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that mothers modify their speech to their young children in ways that support their early language learning through, for example, simplified language that is less complex grammatically, more redundant, and with a higher pitch and exaggerated intonation pattern (Fernald, 1989;Kavanaugh & Jirkovsky, 1982;Kitamura & Burnham, 2003;McRoberts & Best, 1997;Rondal, 1980;Snow, 1977). Numerous studies have found that the diversity of maternal vocabulary may be particularly important in predicting children's later language development and literacy (Bornstein et al, 1998;Hart & Risley, 1995;Hoff-Ginsberg, 1991;Hoff, 2003;Pan et al, 2005;Weizman & Snow, 2001). …”
Section: Parental Language Inputmentioning
confidence: 99%
“…The family environment of the home, as measured by the quality of parent/child interactions, parental language, and the provision of stimulating/sensitive caregiving, has been found to be an important proximal predictor of children's development (Bradley, Corwyn, Burchinal, Pipes-McAdoo, & Garcia Coll, 2001;Hoff-Ginsberg, 1991;Pan, Rowe, Singer, & Snow, 2005;Pancsofar & Vernon-Feagans, 2006; Tamis-Lemonda, Shannon, Cabrera, & Lamb, 2004). These studies have generally shown, through observation and questionnaires, that mothers who are more sensitive and engaging to their children during interactions and provide a more stimulating home environment, have children who are more skilled cognitively, linguistically, and socially.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from the parent-child research suggest that elaborative style during reminiscing is not related to talkativeness or elaborativeness in other contexts such as free play (Fivush et al 2011;Haden and Fivush 1996;Hoff-Ginsburg 1991). Research projects assessing early childhood educator elaborative style during, for example, free play or problem solving would provide a means of comparing these different types of interaction and potentially lead to an understanding of their developmental significance.…”
Section: Future Research Directionsmentioning
confidence: 99%